IODINE CONTENT OF U.S. WEIGHT-LOSS FOOD - Kuriti, Manikya (2014)
OBJECTIVE: The recommended iodine intake is 150 µg/day in adults, 220 µg/day during pregnancy, and 290 µg/day during lactation. Individuals exclusively consuming restricted diets as part of a weight-loss program may be at risk for mild to moderate iodine deficiency. The purpose of this study was to assess the iodine content in meals and snacks from 3 U.S. commercial weight-loss programs, all of which are intended to be the sole source of dietary intake during the desired weight-loss period. METHODS: The iodine contents in the products representing 1 week of all meals and snacks from 3 U.S. commercial weight-loss programs were measured by spectrophotometry. The measured total iodine content in 1 week’s worth of food from each program is reported as an average level per day. RESULTS: A total of 53 total items were analyzed (29 different items [7 breakfasts, 7 lunches, 7 dinners, 6 snacks, 2 desserts] from Jenny Craig(®), 21 different items [7 breakfasts, 7 lunches, 7 dinners] from Nutrisystem(®), and 3 different items [1 breakfast, 1 lunch, 1 dinner; each to be intended to be eaten daily for 1 week] from Medifast(®)). Daily iodine content (mean ± SD) of meals and snacks from the weight-loss programs were 34.2 ± 1.2 (Jenny Craig(®)), 12.2 ± 0.7 (Nutrisystem(®)), and 70.1 ± 1.1 (Medifast) µg/day. CONCLUSION: These results indicate that the dietary content in the foods from 3 U.S. commercial weightloss programs is far less than the recommendations for iodine intake of 150 µg/day in nonpregnant, nonlactating adults. Individuals following each weight-loss program should be advised to take a multivitamin containing 150 µg of iodine daily.